Religious Aspects of Leadership as Seen by Political Anthropology - Skalník, Petr (Univerzita Pardubice, 2007)
Religion and politics are today, as they were in the past, intertwined so that if they do not form an inseparable couple then they are simply a unity which only the analytic eye of the scholar can distinguish. However, there are social processes underway which indicate that the possibilities exist for a society of citizens who do not need to divinize either the state or anyone else, at least not for public purposes. That religion deserves respect is undeniable, especially when it caters for individuals’ balance of personality or those social needs which rationalism cannot fulfil. But together with Gellner and Lessnoff I am of the opinion that it fulfilled its role as ‘the forerunner and progenitor of modernity’. Protestantism and High Islam fulfilled their respective modernizing roles. But in the modern world religion has no ‘legitimate cognitive role’. Science has made claims of religion ‘incredible’ and all reinterpretations of religious modernists deserve ‘no intellectual or moral respect’. Lessnoff credits Gellner with ‘exactly’ mirroring Max Weber’s viewpoint.25 Political anthropology can agree with this provided we also realise that the globalizing world as we experience it today is by far not completed. The tension between those who are marginalised and prepared to believe in leaders and prophets whether genuine or false, and those who arrived to see their modernity as a liberation from religious faith and thus a chance for a self governed truth-seeking civil society, will be there still for a very long time ahead.
Keywords: political anthropology; religion in politics; historical development; African cases; Islamism